Metformin Attenuates Bone Cancer Pain by Reducing TRPV1 and ASIC3 Expression - Qian, He-Ya; Zhou, Fang; Wu, Rui; Cao, Xiao-Jun; Zhu, Tao; Yuan, Hao-Dong; Chen, Ya-Nan; Zhang, Ping-An (Frontiers in Pharmacology, 2021)
Bone cancer pain (BCP) is a common pathologic pain associated with destruction of bone and pathological reconstruction of nervous system. Current treatment strategies in clinical is inadequate and have unacceptable side effects due to the unclear pathology mechanism. In the present study, we showed that transplantation of Walker 256 cells aggravated mechanical allodynia of BCP rats, and the expression of ASIC3 and TRPV1 was obviously enhanced in L4-6 dorsal root ganglions (DRGs) of BCP rats. Additionally, ASIC3 and TRPV1 was mainly expressed in CGRP and IB4 positive neurons of L4-6 DRGs. Further, TRPV1 but not ASIC3 was markedly upregulated in L4-6 spinal dorsal horn (SDH) of BCP rats. Importantly, intrathecal injection of CPZ (a TRPV1 inhibitor) or Amiloride (an ASICs antagonist) markedly increased the paw withdraw threshold (PWT) response to Von Frey filaments of BCP rats. Notably, intraperitoneally injection of Metformin or Vinorelbine markedly elevated the PWT of BCP rats, but reduced the expression of TRPV1 and ASIC3 in L4-6 DRGs and decreased the TRPV1 expression in SDH. Collectively, these results suggest an effective analgesic effect of Metformin on mechanical allodynia of BCP rats, which may be mediated by the downregulation of ASIC3 and TRPV1 in L4-6 DRGs.